The six-eyed sand spiders of the genus Sicarius (Araneae: Haplogynae: Sicariidae) from the Brazilian Caatinga - Magalhães, Ivan L. F.; Brescovit, Antonio D.; Santos, Adalberto J. (Zootaxa, 2013)
In this paper we revise the species of Sicarius (Araneae: Sicariidae) from the Brazilian Caatinga, the largest tropical dry forest nucleus in the world. We redescribe, designate a neotype and provide new records for Sicarius tropicus (Mello- Leitão, 1936), the only species previously known from the region, and describe three new species: S. cariri n. sp., S. diadorim n. sp. and S. ornatus n. sp. We report high intraspecific variation in the genitalic morphology of these species, especially in females. We also provide anecdotal observations on natural history and behavior of these species, including diet, mating behavior and clutch size. We include an identification key for Brazilian Caatinga species of Sicarius.